The Case Tinga: one more episode of racism in South American soccer - Lise, Riqueldi Straub (2015)
The aim of this study was to analyze the discourses about the case of racism against the Brazilian player Paulo Cesar Tinga, that occurred during the soccer match between Asociación Civil Real Atlético Garcilaso (Peru) and Cruzeiro Esporte Clube (Brazil). For this, it was used the theoretical precepts of Discourse Analysis to understand the sources found in sporting periodicals available on the Internet sites. It was possible to infer that the punishment for offenders are too lenient, which turns this type of conduct an ordinary act in the soccer field.